The Constitution of Japan, at the Founding and 50 Years Later - Beer, L W (Victoria University of Wellington Law Review, 1997)
This is a revised version of a paper presented by Professor Beer at a combined meeting of the New Zealand Institute of Public Law and of the New Zealand Association for Comparative Law in the Faculty of Law, Victoria University of Wellington, New Zealand in August 1996. The author explores constitutional issues in Japan after WWII. As the world's prime example of successful synthesis of radically different traditions of law and constitution, the author concludes that Japan deserves global respect and more study in the emerging multi-cultural age.